Numerical modelling of the mechanical behaviour of a fully bio-resorbable glass fibre reinforced composite - Gao, Xi (2019)
Since the advent of sterile surgical procedures, load-bearing metallic implants have been used in surgical procedures for bone fixation purposes. The traditional metallic bone fixation devices, i.e. screws, plates or rods, allow doctors to internally set and stabilize fractured bones, meanwhile, however, are commonly associated with the `stress shielding' effect, which weakens the surrounding bone and increases the risk of re-fracture after the device has been removed. The `stress shielding' effect is caused by the fact that the metallic implants have stiff and stable properties in vivo which is beneficial at the early stage of bone healing because the external load is sustained by the implant and fracture bones are stabilized, however, the fracture bone needs to bear some load in the later healing stage to increase the bone density, whereas the implant shields the fracture bone from receiving load. Implants made of bio-resorbable composite materials provide an opportunity to match the properties of bone whilst transferring load to the healing bone more appropriately, along with being easily formed and their degradation products should be tolerated by the human body. The ideal replacement for traditional metallic bone fixation devices should have excellent biocompatibility, be fully bio-resorbable and have sufficient mechanical properties to support the bone during the early healing stages, before gradually degrading over time. A composite comprising polyactide (PLA) matrix reinforced with phosphate glass fibre (PGF) has been regarded as a desirable replacement of the metallic materials.